Working Hours, Promotion and the Gender Gap in the Workplace - Takao Kato; Hiromasa Ogawa; Hideo Owan (Institute of Labor Economics (IZA), 2016)
This paper presents a novel model of promotion within the firm which sheds new light on the interplay between working hours and the odds of subsequent promotion. The model's key feature is the coexistence of two different sources of asymmetric information: (i) the worker's cost of long working hours: and (ii) the worker's OJT ability (the worker's ability to accumulate valuable human capital on the job through learning by doing). The worker's cost of working long hours is known only to the worker, while the worker's OJT ability is accurately assessed only by the firm observing him/her on the job. Long working hours signal the worker's commitment to the firm, which determines the surplus produced when the worker is promoted. Thus, the firm provides the worker with managerial training only after observing the employee's hours worked, a signal of his/her commitment to the firm or lack thereof. The firm's decision to provide training also depends on its private information about the worker's OJT ability, which affects his/her future productivity if and when the worker gets promoted. Upon completion of training, the firm then promotes the worker. The model illuminates under what conditions, it is efficient for the firm to adopt the information revelation strategy – reveal its private information on the worker's OJT ability to him/her before the worker decides on whether to work long hours and signal his/her commitment. Using the model, we show that under a reasonable set of conditions, the firm may find it optimal to adopt the information revelation strategy for women but not for men, and derive an empirical testable hypothesis that the correlation between working hours and subsequent promotion will be stronger for women than for men. We analyze longitudinal personnel data from a large Japanese manufacturing firm and provide rigorous econometric evidence in support of the hypothesis.
Keywords: M51; J16; 330; working hours; promotion; rat race; adverse selection; and the gender gap